Clay objects as 'tokens'? Evidence for early counting and administration at Late Neolithic Tell Sabi Abyad, Mesopotamia. (2nd September 2018) - Bennison-Chapman, Lucy E.
Abstract : Tell Sabi Abyad was a major Neolithic settlement in Upper Mesopotamia, occupied for 1800 years during the 7th to 6th millennium cal BC. Excavations have revealed hundreds of clay sealings, stamp-seal impressions and an even greater number of small, geometric-shaped clay objects or 'tokens'. Drawing on previous unpublished data from decades of excavations, a detailed, contextual study of the form and distribution of Tell Sabi Abyad's 'tokens' is presented. Though likely used as counting tools in certain specific occupational areas and levels, the evidence does not suggest a singular universal role of geometric clay objects as mnemonic accounting devices.